The financial crisis at the kitchen table: Trends in household debt and credit - Meta Brown; Andrew Haughwout; Donghoon Lee; Wilbert van der Klaauw (Federal Reserve Bank of New York, 2010)
The Federal Reserve Bank of New York (FRBNY) Consumer Credit Panel, created from a sample of U.S. consumer credit reports, is an ongoing panel of quarterly data on individual and household debt. The panel shows a substantial run-up in total consumer indebtedness between the first quarter of 1999 and the peak in the third quarter of 2008, followed by a steady decline through the third quarter of 2010. During the same period, delinquencies rose sharply: Delinquent balances peaked at the close of 2009 and then began to decline again. This paper documents these trends and discusses their sources. We focus particularly on the decline in debt outstanding since mid-2008, which has been the subject of considerable policy and media interest. While the magnitudes of balance declines and borrower defaults, represented as charge-offs on consumers' credit reports, have been similar, we find that debt pay-down has been more pronounced than this simple comparison might indicate.
Keywords: G20; D14; D12; 330; household debt; mortgages; household finance; financial crisis